An Exact Algorithm to Detect the Percolation Transition in Molecular Dynamics Simulations of Cross-Linking Polymer Networks - Livraghi, Mattia; Höllring, Kevin; Wick, Christian; Smith, David M.; Smith, Ana-Suncana (Journal of Chemical Theory and Computation, 2021)
Periodic molecular dynamics simulations are developing to a routine tool for the investigation of complex, polymeric materials. A typical application is the simulation of the curing reaction of covalently cross-linked polymers, which provides detailed understanding of network formation at the molecular scale, with examples including gelation and glass transitions. In this article, we delineate the connection between percolation theory and gel-point detection in periodic polymeric networks. Specifically, we present an algorithm that can detect the onset of percolation during cross-linking of polymers in periodic molecular dynamic simulations. A sample implementation is provided at https://github.com/puls-group/percolation-analyzer. As an example, we apply the algorithm to simulations of an epoxy resin undergoing curing with an amine hardener. We also compare results with indirect gel point measurements obtained from monitoring the growth of the largest mass and the onset of secondary cycles.

Anisotropic molecular diffusion in confinement II: A model for structurally complex particles applied to transport in thin ionic liquid films - Höllring, Kevin; Baer, Andreas; Vučemilović-Alagić, Nataša; Smith, David M.; Smith, Ana-Suncana (Journal of Colloid and Interface Science, 2024)
Hypothesis: Diffusion in confinement is an important fundamental problem with significant implications for applications of supported liquid phases. However, resolving the spatially dependent diffusion coefficient, parallel and perpendicular to interfaces, has been a standing issue and for objects of nanometric size, which structurally fluctuate on a similar time scale as they diffuse, no methodology has been established so far. We hypothesise that the complex, coupled dynamics can be captured and analysed by using a model built on the 2-dimensional Smoluchowski equation and systematic coarse-graining. Methods and simulations: For large, flexible species, a universal approach is offered that does not make any assumptions about the separation of time scales between translation and other degrees of freedom. The method is validated on Molecular Dynamics simulations of bulk systems of a family of ionic liquids with increasing cation sizes where internal degrees of freedom have little to major effects. Findings: After validation on bulk liquids, where we provide an interpretation of two diffusion constants for each species found experimentally, we clearly demonstrate the anisotropic nature of diffusion coefficients at interfaces. Spatial variations in the diffusivities relate to interface-induced structuring of the ionic liquids. Notably, the length scales in strongly confined ionic liquids vary consistently but differently at the solid–liquid and liquid–vapour interfaces.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Anisotropic diffusion; Diffusion at interfaces; Diffusion in films; Ionic liquids; Molecular liquids; Transport coefficient

Anisotropic molecular diffusion in confinement I: Transport of small particles in potential and density gradients - Höllring, Kevin; Baer, Andreas; Vučemilović-Alagić, Nataša; Smith, David M.; Smith, Ana-Suncana (Journal of Colloid and Interface Science, 2023)
Hypothesis: Diffusion in confinement is an important fundamental problem with significant implications for applications of supported liquid phases. However, resolving the spatially dependent diffusion coefficient, parallel and perpendicular to interfaces, has been a standing issue. In the vicinity of interfaces, density fluctuations as a consequence of layering locally impose statistical drift, which impedes the analysis of spatially dependent diffusion coefficients even further. We hypothesise, that we can derive a model to spatially resolve interface-perpendicular diffusion coefficients based on local lifetime statistics with an extension to explicitly account for the effect of local drift using the Smoluchowski equation, that allows us to resolve anisotropic and spatially dependent diffusivity landscapes at interfaces. Methods and simulations: An analytic relation between local crossing times in system slices and diffusivity as well as an explicit term for calculating drift-induced systematic errors is presented. The method is validated on Molecular Dynamics simulations of bulk water and applied to simulations of water in slit pores. Findings: After validation on bulk liquids, we clearly demonstrate the anisotropic nature of diffusion coefficients at interfaces. Significant spatial variations in the diffusivities correlate with interface-induced structuring but cannot be solely attributed to the drift induced by local density fluctuations.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Anisotropic diffusion; Diffusion at interfaces; Diffusion in pores; Drift and density gradient; Porous materials; Transport coefficient

Capturing the mechanosensitivity of cell proliferation in models of epithelium - Höllring, Kevin; Nuić, Lovro; Rogić, Luka; Kaliman, Sara; Gehrer, Simone; Wollnik, Carina; Rehfeldt, Florian; Hubert, Maxime; Smith, Ana-Suncana (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Despite the primary role of cell proliferation in tissue development and homeostatic maintenance, the interplay between cell density, cell mechanoresponse, and cell growth and division is not yet understood. In this article, we address this issue by reporting on an experimental investigation of cell proliferation on all time- and length-scales of the development of a model tissue, grown on collagen-coated glass or deformable substrates. Through extensive data analysis, we demonstrate the relation between mechanoresponse and probability for cell division, as a function of the local cell density. Motivated by these results, we construct a minimal model of cell division in tissue environment that can recover the data. By parameterizing the growth and the dividing phases of the cell cycle, and introducing such a proliferation model in dissipative particle dynamics simulations, we recover the mechanoresponsive, time-dependent density profiles in 2D tissues growing to macroscopic scales. The importance of separating the cell population into growing and dividing cells, each characterized by a particular time scale, is further emphasized by calculations of density profiles based on adapted Fisher–Kolmogorov equations. Together, these results show that the mechanoresponse on the level of a constitutive cell and its proliferation results in a matrix-sensitive active pressure. The latter evokes massive cooperative displacement of cells in the invading tissue and is a key factor for developing large-scale structures in the steady state.
CRIS-Team Scopus Importer:2024-11-29
Keywords: cell division in tissue environment; dissipative particle dynamics; epithelial tissue; Fisher–Kolmogorov equation

Morphology as indicator of adaptive changes of model tissues in osmotically and chemically changing environments - Höllring, Kevin; Vurnek, Damir; Gehrer, Simone; Dudziak, Diana; Hubert, Maxime; Smith, Ana-Suncana (Biomaterials Advances, 2023)
We investigate the formation and maintenance of the homeostatic state in the case of 2D epithelial tissues following an induction of hyperosmotic conditions, using media enriched with 80 to 320 mOsm of mannitol, NaCl, and urea. We characterise the changes in the tissue immediately after the osmotic shock, and follow it until the new homeostatic state is formed. We characterise changes in cooperative motility and proliferation pressure in the tissue upon treatment with the help of a theoretical model based on the delayed Fisher-Kolmogorov formalism, where the delay in density evolution is induced by the the finite time of the cell division. Finally we explore the adaptation of the homeostatic tissue to highly elevated osmotic conditions by evaluating the morphology and topology of cells after 20 days in incubation. We find that hyperosmotic environments together with changes in the extracellular matrix induce different mechanical states in viable tissues, where only some remain functional. The perspective is a relation between tissue topology and function, which could be explored beyond the scope of this manuscript. Experimental investigation of morphological effect of change of osmotic conditions on long-term tissue morphology and topology Effect of osmotic changes on transient tissue growth behaviour Analysis of recovery process of tissues post-osmotic-shock Toxicity limits of osmolytes in mid- to long-term tissue evolution Tissue adaptation to physiological changes in environment Long-term tissue stabilisation under altered osmotic conditions.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Epithelium topology and morphology; Fisher-Kolmogorov theory; Hyperosmotic conditions; Model tissue development; Tissue adaptation